Superior Semicircular Canal Dehiscence – An Otologic Impersonator - Carção, André (2021)
Objectives: to identify common clinical characteristics in patients with superior semicircular canal dehiscence (SSCD)in order to increase the diagnostic suspicion of this recently described clinical entity. Materials and Methods: a retrospective analysis was carried out between 2016 and 2019 and 5 cases were analyzed, corresponding to 8 ears with SSCD, analyzing the accompanying symptoms. The diagnosis of dehiscence was established through computed tomography (CT) of the temporal bone. Results: Hearing loss was the major complaint being common to all patients. In the 8 ears analyzed, there was a predominance of conduction hearing loss in frequencies below 1000Hz with normal impedance audiometry. Conclusions: the recognition of these patients, with a third non-physiological window in the bony lining of the superior semicircular canal, makes possible a differential diagnosis that explains a conduction or mixed hearing loss with acoustic reflexes present, thus preventing errors in diagnosis and unnecessary surgery.